Risks associated with the acquisition of tuberculosis in workers in a Micro Insurance network - Bautista Benito, Guisella Romy (2019)
Objective. To determine the risk of becoming ill with tuberculosis. comparative, transversal study with a quantitative research approach, made up of 255 workers, grouped in six (6) health facilities of the Jaime Zubieta calderon health micro-network- San Juan de Lurigancho health network, during the period 2016 and 2017. a data collection sheet was used, based on “the checklist for the implementation of the institutional tuberculosis infection control plan (iticp) in hospitals and health centers”. inferential analysis was performed using the chi square goodness of fit test. Results. With respect to the workers, 83.5 % were between 30 and 59 years old, 71 % were female, 60.8 % were permanent work status and in the occupational group nursing technicians predominated (29.8 %). on the other hand, two health facilities (50 %) managed to answer the list of 14 questions in the affirmative. and, significant differences were found in comparing the proportion of positive responses with the ideal response value of 0.75 per health facility (p < 0.05). Conclusions. There is a risk of getting sick with tb in the health personnel of the first level of attention, of the jaime zubietacalderon health micro-network – san juan de lurigancho health center.